INVESTIGATING THE IMAGE OF A TOURIST DESTINATION: THE CASE OF SAARISELKÄ - Cristina VIJOLI; Nicolae MARINESCU (Studia Universitatis Babeș-Bolyai Negotia, 2017)
This paper emphasizes the importance of defining a precise image for a tourist destination. We review first the main contributions in the literature on tourist destinations and their marketing. Then, we outline the methodology of a marketing research conducted in Saariselkä, a resort located in northern Finland. The results of the research provide interesting insights on how the image of this particular destination is perceived by tourists. The findings of the research also enable us to draw several conclusions which may prove useful for an enhanced efficiency of the promotional efforts. JEL Classification: L83